Anterior lamellar recession for management of upper eyelid cicatricial entropion and associated eyelid abnormalities - Tamer I.Gawdat; Mahmoud A. Kamal; Ahmed S.Saif; Mostafa M. Diab (International Journal of Ophthalmology, 2017)
AIM: To evaluate the functional and aesthetic outcomes of upper eyelid cicatricial entropion (UCE) correction using anterior lamellar recession (ALR) with addressing the associated conditions including dermatochalasis, brow ptosis, blepharoptosis, and lid retraction. METHODS: Chart review of patients with upper lid cicatricial entropion who had undergone ALR from 2013 to 2016 was reviewed. Success was defined as the lack of any lash in contact with the globe, no need for a second procedure, and acceptable cosmesis at the final follow up. RESULTS: Sixty eight patients (97 eyelids) were operated by ALR with simultaneous correction of associated lid problems in each case when necessary. The mean follow-up time was 17.8mo (range, 6.0-24.0mo). Concomitantly, levator tucking was performed in 19 eyelids (19.6%), upper lid retractor recession in 18 eyelids (18.6%), and internal browpexy in 31 eyelids (32.0%). In 95.8% of patients (95%CI: 0.85-0.96), satisfactory functional and cosmetic outcome was achieved with a single surgical procedure. CONCLUSION: Based on the principles of lamellar recession and concurrently addressing the associated lid problems, this approach is an effective and safe treatment of UCE.